Tracheitis in a Broiler Chicken Flock Caused by Dual Infection with Cryptosporidium spp. (Apicomplexa: Cryptosporiidae) and Non-hemolytic Ornithobacterium rhinotracheale - Gornatti Churria, Carlos Daniel (2012)
Broiler chickens aged 41-day-old from a flock of a broiler complex, presenting depression, reduced food intake, facial edema, dyspnea, gasping, sneezing, and 5% mortality were studied. At necropsy, opaque thoracic and abdominal air sacs and mucous tracheal content were observed. Histopathology of tracheas showed multifocal hyperplasia of mucosa with a large number of small, round and ovoid basophilic organisms on their surface, which were identified as Cryptosporidium spp. In addition, there was an inflammatory response due to infiltration of mononuclear cells and heterophils in the submucosa. Small pin-point colonies without hemolytic activity were isolated from tracheal samples and identified as Ornithobacterium rhinotracheale by conventional and real time polymerase chain reaction (PCR). Results of tracheal histopathology, bacteriology, and PCR identification provided the diagnosis of tracheal cryptosporidiosis associated with non-hemolytic O. rhinotracheale secondary infection. This report describes the unusual dual infection with Cryptosporidium spp. and non-hemolytic O. rhinotracheale causing tracheitis in broiler chickens.